A method for testing the effect of management interventions on the satisfaction and loyalty of national park visitors. (14th March 2016) - Taplin, Ross H.; Rodger, Kate; Moore, Susan A.
Abstract: Providing visitors with satisfying experiences is integral to park management. Research has inferred the determinants of satisfaction and loyalty through theorizing, observational studies, and statistical correlations. This article advocates randomized experiments as a complementary method for testing the causal effect of selected management interventions that change service quality on satisfaction and loyalty. An experiment using ranger presence and enhanced toilets in a West Australian national park is used to illustrate the approach. The presence of rangers caused significantly improved satisfaction with rangers, related service quality attributes, and overall satisfaction, but not loyalty. Enhancing toilets had nonsignificant impacts. These results strongly suggest the need for further visitor-focused experimental research to complement the growing body of research in national parks investigating the complex relationship among service quality, satisfaction, and loyalty.